Forensic analysis of computer memory. (O'Reilly Media, Inc., 2017)
Our connected world today generates unimaginable volumes of data, and sometimes that information can be the key to helping law enforcement and corporate investigators solve crimes or reveal intrusions by hackers into a network. Memory analysis is important for incident responders and cases for which there is essential evidence that could be lost when a system is powered off. Fortunately, there are a number of tools that we can use to help with memory analysis. In this course, entry- to intermediate-level IT professionals as well as law enforcement personnel can learn to use tools like Volatility and Rekall to acquire memory images from Windows, Linux, and macOS systems and examine them for signs of malware and other abnormalities. You'll see the techniques needed to conduct digital forensic work, such as identifying running processes, and more.